2014
DOI: 10.1155/2014/568141
|View full text |Cite
|
Sign up to set email alerts
|

Production and Partial Purification of Alpha Amylase fromBacillus subtilis(MTCC 121) Using Solid State Fermentation

Abstract: Amylase is an enzyme that catalyzes the breakdown of starch into sugars and plays a pivotal role in a variety of areas like use as digestives, for the production of ethanol and high fructose corn syrup, detergents, desiring of textiles, modified starches, hydrolysis of oil-field drilling fluids, and paper recycling. In the present work, solid state fermentation (SSF) for α-amylase production has been used in lieu of submerged fermentation (SmF) due to its simple technique, low capital investment, lower levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 31 publications
3
40
1
1
Order By: Relevance
“…Enzyme activity was 100% at 40°C for strain ARMATI. The finding totally agree with the study of Raul et al (2014) and Deb et al (2013), who examined the effect of temperature on amylase activity from Bacillus strains and observed maximum enzyme activity at 40°C. However, our study was against the finding of Teodoro and Martins (2000), who found that amylase produced by Bacillus sp.…”
supporting
confidence: 92%
“…Enzyme activity was 100% at 40°C for strain ARMATI. The finding totally agree with the study of Raul et al (2014) and Deb et al (2013), who examined the effect of temperature on amylase activity from Bacillus strains and observed maximum enzyme activity at 40°C. However, our study was against the finding of Teodoro and Martins (2000), who found that amylase produced by Bacillus sp.…”
supporting
confidence: 92%
“…The alpha amylase activity declines on the both side at 24 hours and at 72 hours with activity 970 ± 7.3 U/g and 1050 ± 9.8 U/g respectively ( Figure 1). The value can be correlated with the results of other workers supporting highest amylase production after 48 hours fermentation period [20]. Earlier study depicts that a clear correlation exists between bacterial growth and alpha amylase production [23].…”
Section: Effect Of Fermentation Hours On Amylase Production During Sosupporting
confidence: 85%
“…The moisture level of the wheat bran is kept at 50% (w/w) with autoclaved distilled water. The contents of the flask are autoclaved prior to solid state fermentation [20].…”
Section: Methodsmentioning
confidence: 99%
“…(Ben Massoud et al, 1999). Prakash& Jaiswal, (2009), Raul et al, (2014) and Saxena et al (2007) referred that a commercial production of thermostable and alkaline α-amylases were produced by mesophile Bacillus sp. as Bacillus subtilis, Bacillus stearothermophilus, Bacillus licheniformis, and Bacillus amyloliquefaciens which have large applications.…”
Section: Introductionmentioning
confidence: 99%